HUBUNGAN BEBAN KERJA, BUDAYA KERJA DAN LAMA KERJA TERHADAP STRES KERJA PERAWAT DI RUANG IRNA III RUMAH SAKIT UMUM DAERAH DR.H. ABDUL MOELOEK PROVINSI LAMPUNG - Usastiawaty Cik Ayu Saadiah Isnainy; Prima Dian Furqoni; Lidya Ariyanti; Leni Sari Asdi (Universitas Malahayati Lampung, 2019)
ABSTRACT: RELATIONSHIP OF WORK LOADS, WORK CULTURE AND OLD WORK TOWARDS NURSING WORK STRESS IN IRNA III REGIONAL GENERAL HOSPITALS Dr. ABDUL MOELOEK PROVINSI LAMPUNG Background: The effect of work stress on nurses influences the professionalism of nurses in serving patients. Based on the results of prasurvey on December 1 to 4, 2017, it was found out from 15 nurses at RSUDAM 73.3% of nurses stated that they were saturated with routine and tiring, 66.7% of the work culture in hospitals made a burden of mind and the majority of nurses worked more than 10 years 73.3%.Purpose: to determine the relationship between burden, duration of work, culture and stress between nursing at irna III ward-dr.h. Abdul Moeloek Lampung Lampung Province General Hospital 2018.Methods: This research is a quantitative research, using Analytical Survey method with Cross Sectional approach. Research will be conducted after the proposal exam is approved. The population in this study were all nurses in the Irna III Room Abdul Moeloek Regional General Hospital totaling 250 people, a sample of 154 people. Sampling techniques with Purposive Sampling. Data collection using questionnaire sheets. Data processing editing, coding, processing, cleaning. Data analysis using univariate and bivariate (Chi Square).Results: Based on the results it is known that as many as 1 26 (16.9%) respondents experienced work stress. 102 (66.2%) respondents had a light workload. as many as 95 (61.7%) respondents of good organizational culture, as many as 117 (76.0%) old respondents in working.Conclusion: There is a relationship between workload (p-value = 0,000 or 6,221), There is a relationship between organizational culture (p-value = 0,014 or 3,163), There is a relationship between length of work (p-value = 0,000 or 5,326) with the stressful incidence of nurse work. It is expected that the hospital will provide activities such as recreation for employees and families Keywords: Expenses, Culture, Length of work, stress, nurses INTISARI: HUBUNGAN BEBAN KERJA, BUDAYA KERJA DAN LAMA KERJA TERHADAP STRES KERJA PERAWAT DI RUANG IRNA III RUMAH SAKIT UMUM DAERAH DR.H. ABDUL MOELOEK PROVINSI LAMPUNG Latar Belakang: Pengaruh stres kerja pada perawat berpengaruh terhadap profesionalisme perawat dalam melayani pasien. Berdasarkan hasil prasurvey tanggal 1 - 4 Desember 2017, diketahui dari 15 perawat di RSUDAM 73,3% perawat menyatakan jenuh dengan rutinitas yang dilakukan dan terasa melelahkan, 66,7% budaya kerja di rumah sakit membuat beban pikiran dan mayoritas Perawat telah bekerja lebih dari 10 tahun 73,3%.Tujuan: untuk mengetahui hubungan antara beban, lama kerja, budaya dan stres di antara keperawatan di irna III ward- dr.h. Abdul Moeloek Lampung Rumah Sakit Umum Provinsi Lampung 2018Metode Penelitian : Penelitian ini merupakan penelitian kuantitatif, menggunakan metode Survey Analitik dengan pendekatan Cross Sectional. Penelitian akan dilaksanakan setelah ujian proposal disetujui. Populasi dalam penelitian ini adalah seluruh perawat di Ruang Irna III Rumah Sakit Umum Daerah Abdul Moeloek berjumlah 250 orang, sampel 154 orang. Teknik Pengambilan sampel dengan Purposive Sampling. Pengumpulan data menggunakan lembar kuesioner. Pengolahan data editing, coding, processing, cleaning. Analisis data dengan secara univariat dan bivariat (Chi Square).Hasil: Berdasarkan hasil diketahui bahwa sebanyak 1 26 (16,9%) responden mengalami stres kerja. sebanyak 102 (66,2%) responden memiliki beban kerja ringan. sebanyak 95 (61,7%) responden budaya organisasi baik, sebanyak 117 (76,0%) responden lama dalam bekerja.Kesimpulan: Ada hubungan antara beban kerja (p-value = 0,000 or 6,221), Ada hubungan antara budaya organisasi (p-value = 0,014 or 3,163), Ada hubungan antara lama bekerja (p-value = 0,000 or 5,326) dengan kejadian stres kerja perawat. Diharapkan pihak rumah sakit Memberikan kegiatan seperti rekreasi bagi karyawan dan keluarga Kata kunci : Beban, Budaya, Lama bekerja, stress, perawat